Development and psychometric evaluation of the Anticipated Food Scarcity Scale (AFSS) - FOLWARCZNY, Michal (Institutional Knowledge at Singapore Management University, 2021)
Mass media extensively inform societies about events threatening the global food supply (e.g., pandemics or Brexit). Consumers exposed to such communication may perceive food resources as becoming scarcer. In line with an evolutionary account, these perceptions can shift decision-making in domains such as food preferences or prosociality. However, existing literature has solely focused on actual and past food insecurity experiences threatening mostly low-income families, thus neglecting the future-oriented perceptions among the general population. This paper broadens the food insecurity research scope by developing a new construct-anticipated food scarcity (AFS)-which is defined as the perception that food resources are becoming less available (in the future). We have developed and psychometrically validated the 8-item Anticipated Food Scarcity Scale (AFSS) in eight studies (N = 1333). The 8-item AFSS is unidimensional and has good psychometric qualities. The scale is sensitive to food scarcity cues and, therefore, can be used in experimental research. Moreover, its relatively narrow set of items makes it an exceptionally potent tool for use in online surveys, field settings, and lab studies. Taken together, the AFSS presents an alternative approach to food scarcity measurement in affluent societies and, consequently, can foster novel research on food waste, prosocial behaviors, and other similar topic areas.